2005
DOI: 10.1254/jphs.fpj05004x
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanism of Combined Effect of Methamphetamine and Morphine on Lethality in Mice and Therapeutic Potential of Cooling

Abstract: An increase in polydrug abuse is a major problem worldwide. A previous study showed that coadministration of methamphetamine and morphine induced lethality in rodents and humans. However, the underlying mechanisms by which the lethality is increased by the coadministration of methamphetamine and morphine have not been fully understood. Therefore, the present study was designed to determine the mechanism of increased lethality induced by methamphetamine and morphine. Coadministered methamphetamine and morphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Furthermore, the incidence of methamphetamine-induced self-injurious behavior might be a valid marker of long-term toxicity (23). A recent study showed that coadministration of 20 mg / kg of methamphetamine and 20 mg / kg of morphine induced lethality in BALB / c mice, which may be mediated by activation NMDA receptors (42). Methamphetamine-induced hyperthermia is one of the markers of methamphetamine-induced neurotoxicity; interestingly, morphine (which itself induced hyperthermira) enhanced hyperthermira induced by 20 mg / kg of methamphetamine (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the incidence of methamphetamine-induced self-injurious behavior might be a valid marker of long-term toxicity (23). A recent study showed that coadministration of 20 mg / kg of methamphetamine and 20 mg / kg of morphine induced lethality in BALB / c mice, which may be mediated by activation NMDA receptors (42). Methamphetamine-induced hyperthermia is one of the markers of methamphetamine-induced neurotoxicity; interestingly, morphine (which itself induced hyperthermira) enhanced hyperthermira induced by 20 mg / kg of methamphetamine (42).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that coadministration of 20 mg / kg of methamphetamine and 20 mg / kg of morphine induced lethality in BALB / c mice, which may be mediated by activation NMDA receptors (42). Methamphetamine-induced hyperthermia is one of the markers of methamphetamine-induced neurotoxicity; interestingly, morphine (which itself induced hyperthermira) enhanced hyperthermira induced by 20 mg / kg of methamphetamine (42). However, it is not yet clear whether morphine can affect methamphetamine-induced neurotoxicity or not.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that methamphetamine-induced neurotoxicity is associated with NMDA-receptor activation, NOS activation, the formation of oxygen-based free radicals and the activation of poly (ADP-ribose) polymerase (PARP) (Cosi et al, 1996;Xia et al, 1996;Yamamoto and Zhu, 1988;Kita et al, 2003). In our previous study, we demonstrated that blocking of NMDA receptors, but not NOS inhibitors, significantly suppressed the lethality induced by the coadministration of methamphetamine and morphine (Namiki et al, 2005). Therefore, these results indicate that NO may not be related to the increased lethality induced by the coadministration of methamphetamine and morphine.…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that lethality is enhanced by the coadministration of methamphetamine and morphine in humans and rodents (Funahashi et al, 1998;Uemura et al, 2003;Namiki et al, 2005). We previously demonstrated that pretreatment with NMDA receptor antagonists and immediate and/or continuous cooling, which may mediate a reduction in the release of free radicals, significantly attenuated the increased subacute toxicity or lethality induced by the coadministration of methamphetamine and morphine (Namiki et al, 2005). In our opinion, knowledge to know about golden time for cooling may help in improving the therapy for toxicosis in emergency medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The first is mediated by glutamate receptors. Overstimulation of glutamate receptors causes injury or death of neurons by a mechanism termed excitotoxicity (8,9). ROS production, as well as mitochondrial Ca 2+ overload, mitochondrial depolarization and ATP depletion, is one of the important mechanisms underlying the excitotoxic damage of neurons (10,11).…”
Section: Introductionmentioning
confidence: 99%